Dampak Adopsi IFRS terhadap Panjang Laporan Keuangan Perusahaan yang terdaftar di Bursa Efek Indonesia - Muanas, Muanas; Garini, Zahra Argadia (Jurnal Ilmiah Akuntansi Kesatuan, 2017)
As a member of G-20 Forum, Indonesia starts to adopts the International Financial Reporting Standard (IFRS) as a requirement to fulfill the demands and needs of financial statements users. The adoption of international accounting standards into national accounting standards aim to create financial statements that have high level of credibility and accountability. IFRS requests the requirement of high level of disclosure items so the value of companies will increase, management will have high level of accountability to run the company, that allows changes on the financial statements, for example that can change the length of financial statements. The purpose of this study is to know the effect of IFRS adoption on the length of financial statements, and to know the content of financial statements before and after IFRS adoption. This study was conducted by dividing financial statements into two sections, which are major statements and notes to the financial statements. The financial statements used in this study are 2008 and 2013. The sample was selected by purposive sampling method and analyzed using parametric and non-parametric tests. Results of this study show that major statements and notes to the financial statements experienced an increase in length after adopting IFRS. Notes to financial statements experiencing the most significant increase in length after adopting IFRS. On the major statements, the increase is caused by other comprehensive income account. While on the notes to the financial statements, increase is caused by implementation of PSAK 1 which requires the high level of disclosures. The increase mainly occured in accounting policy on the financial statements.